Effect of itraconazole on the safety and pharmacokinetics of antitumor SHR6390 - Lv, Xiaozhi; Wu, Junyan; Yao, Herui; Ye, Suiwen; Zhang, Nan (Frontiers in Drug Discovery, 2022)
The experimental drug SHR6390 has anti-tumor activity as a cyclin dependent kinase 4/6 inhibitor and is metabolized primarily by the cytochrome P450 3A4 enzyme. Therefore, The purpose of this trial was to evaluate the safety and pharmacokinetics of SHR6390, a potent cytochrome P450 3A4 inhibitor, in healthy Chinese subjects. In this trial study, 18 subjects received a single oral dose of SHR6390 50mg on day 1, multiple doses of 200 mg itraconazole on days 12-24 for 13 days, and a single oral dose of SHR6390 50mg on day 15. After coadministration with itraconazole, the maximum plasma concentration (Cmax) of SHR6390 increased by 70.7%(from 14.3 ng/mL to 24.5 ng/mL), and the area under the time curve from 0 to T (AUC0-T) increased by 110.8% from 468 h∙ng/mL to 988 h∙ng/mL. The area under the concentration-time curve extrapolated to ∞(AUC0-∞) increases from 509 H ∙ng/mL to 1040 h∙ng/mL, an increase of 105.1%. Oral gap (CL/F) decreased (47.9 L/h and 98.3 L/h) and apparent volume of distribution (Vz/F) decreased (4190 L and 5890 L). According to common terminology criteria, 15 32 adverse events were reported in 18 subjects (AEs) (27 SHR6390-related AEs and 15 Itraconazole-related AEs), AEs were all Class 1 adverse events.Overall, co-administration of Itraconazole increased the plasma exposure of SHR6390 in healthy subjects. Both SHR6390 alone and co-administration of Itraconazole showed acceptable safety profiles, which warrants further investigation.